Identification of Meaning and Value in Toraja Carving on the Ornamental Variety of Flora as a Source Character Education - Hendrik Hendrik; Novalia Sulastri (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to identify the Meaning and Value of Toraja Carving in the Ornamental Variety of Flora Carvings as a Source of Character Education. Toraja carving is one of the original Toraja traditional arts that are usually found on the walls of Tongkonan houses (Toraja traditional houses) and Alang (rice barns). Toraja carvings are referred to as “Passura”. This research is qualitative research and the type of research is descriptive. The results of the research obtained are the meaning and value of character education contained in Toraja carving as a variety of ornamental flora carvings. The meaning contained in every Toraja carving is that the family in “Tongkonan” is facilitated in seeking fortune, in life it is expected to always be calm and abundant in rice, always maintain the ropes of brotherhood, always maintain the mind and nobleness, the owner of the traditional house (Tongkonan) has fertile and vast rice fields, we must obey so that we always get protection from the Creator, must not be convoluted when talking, symbolizes joy and gratitude, always maintains unity, is always humble, cultivates unity so that the work becomes light. The values contained in each Toraja carving are religious, peace-loving, honest, caring for the environment, hard work, aggressing achievements, and creative.